Techno-economic analysis of sustainability and externality costs of water desalination production. (October 2021) - Saleh, Layla; Mezher, Toufic
Abstract: Increase in economic activities and population growth have resulted in the high energy and water demands which made them top priorities for many countries around the globe. This led to exploring new sources for producing fresh water including desalination. Estimating the true cost of desalinated water production should include both internal and externality costs. The objective of this paper is to calculate the externality costs that are associated with desalination water production in United Arab Emirates. The study examines and quantifies the environmental, economical and social costs of thermal desalination plants for both Multi-Effect Distillation (MED) and Multi-Stage Flash (MSF) technologies using Analytical Hierarchy Process model. For this purpose, various desalination sustainability criteria that are considered include CO2 emissions, brine discharge, chemicals pollutants, land area, employment rate, desalinated water quality and water availability. Results show that the true cost of desalinated water production almost doubled when the externality costs are included. Results indicated that the externality costs for the MED technology ranged between 0.297$/m3 and 0.702 $/m3 leading to an average increase of 65.8%. For the MSF technology, the externality costs ranged between 0.548$/m3 and 1.174$/m3 leading to an average increase is of 81.9%. Highlights: Environmental, social and economic consequences of water desalination. Air, Water, and Solid Waste Pollutions from desalination processes. Externality and true costs of MED and MSF desalination technologies. Analytical Hierarchy Process decision model used to calculate externality costs. Externality costs for the MED technology ranged 0.297$/m3 and 0.702 $/m3. Externality costs for MSF technology the costs ranged between 0.548$/m3 and 1.174$/m3.